2022
DOI: 10.3390/foods11233835
|View full text |Cite
|
Sign up to set email alerts
|

Role of Intramuscular Connective Tissue in Water Holding Capacity of Porcine Muscles

Abstract: Background: This study evaluated the influence of intramuscular connective tissue (IMCT) on structural shrinkage and water loss during cooking. Longissimus thoracis (LT), semimembranosus (SM) and semitendinosus (ST) muscles were cut and boiled for 30 min in boiling water, followed by detection of water holding capacity (WHC), tenderness, fiber volume shrinkage and protein denaturation. Results: Compared with LT and SM, ST had the best WHC and lowest WBSF and area shrinkage ratio. The mobility of immobilized wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…This suggests a positive correlation between muscle fiber density and indicators such as hardness and chewiness, similar to findings from Jia's study [11]. Conversely, the lower fiber density and higher connective tissue content in the TPI group reduce texture properties such as hardness and springiness while inhibiting moisture loss, resulting in a softer texture and higher moisture content in TPI-group meat [21,25]. According to Luo's result, reduced muscle hardness impacts meat quality, while improvements in hardness, chewiness, and springiness enhance meat quality, indicating that IPRS plays a positive role in improving muscle texture properties and meat quality [29].…”
Section: Effects Of Different Aquaculture Modes On the Physical Prope...supporting
confidence: 84%
See 1 more Smart Citation
“…This suggests a positive correlation between muscle fiber density and indicators such as hardness and chewiness, similar to findings from Jia's study [11]. Conversely, the lower fiber density and higher connective tissue content in the TPI group reduce texture properties such as hardness and springiness while inhibiting moisture loss, resulting in a softer texture and higher moisture content in TPI-group meat [21,25]. According to Luo's result, reduced muscle hardness impacts meat quality, while improvements in hardness, chewiness, and springiness enhance meat quality, indicating that IPRS plays a positive role in improving muscle texture properties and meat quality [29].…”
Section: Effects Of Different Aquaculture Modes On the Physical Prope...supporting
confidence: 84%
“…This indicates that the TPI group has a higher WHC, related to the connective tissue between muscle fibers. Studies have shown that an increase in connective tissue in muscles can enhance the ability to retain moisture and prevent juice loss [20]; when muscle is compressed or cooked and contracts, a certain amount of connective tissue reduces water mobility, retaining water within the muscle tissue [21]. The significantly lower WHC in the IPRS group is linked to its low connective tissue content, differing from the general assumption that high muscle fiber density correlates with high WHC, proving that WHC is also constrained by muscle connective tissue, forming a prerequisite for water retention that includes both muscle fiber density and connective tissue elements [22].…”
Section: Effects Of Different Aquaculture Modes On the Physical Prope...mentioning
confidence: 99%
“…Moreover, as meat is subjected to extended cooking times, the proteins undergo further structural modifications, such as denaturation and cross-linking, which can affect their water-binding capacity and overall texture. Therefore, the combination of collagen's water-retaining properties and alterations in protein structure due to prolonged heating likely influences the cooking loss and texture of the cooked meat ( Wang et al, 2022 ). Conventional heat treatment methods (oven roasting, boiling, pan frying, stewing, grilling, microwave cooking,) are characterized by higher cooking loss from goose meat (34.2–52.2%) ( Wołoszyn et al, 2020 ; Wereńska, 2023 ) compared to the sous-vide method used in this work in a combination of three times and 2 temperatures (19.1–43.9%).…”
Section: Resultsmentioning
confidence: 99%
“…For the water holding capacity (WHC), we observed that cooking loss and the proportion of free water were positively correlated (p < 0.05) with total collagen content, HP crosslinking, decorin content, and denaturation temperature of IMCT, and negatively correlated (p < 0.05) with collagen solubility and content of α-helix and β-sheet in IMCT. Similarly, Wang et al [57] have indicated that pork semitendinosus muscle had better WHC than longissimus thoracis and semimembranosus muscles, though they showed lower contents of cross-links and decorin. Shear force and hardness were positively correlated (p < 0.05) with total collagen content, HP crosslinking and decorin content, and negatively correlated (p < 0.05) with collagen solubility.…”
Section: Correlation Analysismentioning
confidence: 89%